Impact of climate change on water resources of upper Kharun catchment in Chhattisgarh, India - Tischbein, B. (2020)
This research aims to assess the impact of climate change on water balance components. Hydrological simulations, performed by SWAT (Soil and Water Assessment Tool), indicate over-proportional runoff-rainfall and under-proportional percolation-rainfall relationships. Simulated annual discharge for 2020s will decrease by 2.9% on average (with a decrease of 25.9% for q1 to an increase by 23.6% for q14); for 2050s an average increase by 12.4% (17.6% decrease for q1 to 39.4% increase for q0). Respective ranges on percolation: for 2020s an average decrease by 0.8% (12.8% decrease for q1 to an increase of 8.7% for q14); for 2050s an average increase by 2.5% (10.3% decrease for q1 to 15.4% increase for q0). These over- and under-proportional relationships indicate future enhancement of floods and question sufficiency of groundwater recharge.